2018
DOI: 10.1111/nep.13054
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues in using eculizumab for children with atypical haemolytic uraemic syndrome in the acute phase: A review of four patients

Abstract: Eculizumab, the first line treatment for children with aHUS, is usually effective. However, certain problems associated with its use require caution to be exercised. As clinical information on eculizumab are still very limited, and the rationale for its long-term use has yet to be established, physicians are advised to exercise care when using eculizumab to manage aHUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Eculizumab demonstrated a high efficacy in patients with hemoglobinopathy ( Table 1 ). Despite its efficacy, infusion reactions have been reported and eculizumab has been shown to increase the risk of infection by encapsulated organisms, leading ideally to a meningococcal vaccination at least 2 weeks prior the initiation of therapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eculizumab demonstrated a high efficacy in patients with hemoglobinopathy ( Table 1 ). Despite its efficacy, infusion reactions have been reported and eculizumab has been shown to increase the risk of infection by encapsulated organisms, leading ideally to a meningococcal vaccination at least 2 weeks prior the initiation of therapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, prophylaxis with various antibiotics has been performed to prevent infection in infants with aHUS undergoing eculizumab therapy before meningococcal vaccination [8][9][10][11][12][13]. There are the following three reports on infants who are at least 2 months old and qualified for eculizumab therapy [1]: amoxicillin prophylaxis was implemented until 2 weeks after vaccination (MCV4-TT; Nimenrix ® ) in a 3-month-old infant [8]; in a 4-month-old infant, prophylactic administration of cefdinir was started at the beginning of eculizumab therapy, and vaccination (MCV4-DT; Menactra ® ) was performed 2 weeks later (6 months after birth) and 17 weeks later (9 months after birth) [9]; and prophylactic antibiotics such as ampicillin were given to five infants aged 3-6 months until at least 2 weeks after vaccination [10]. Based on the findings from previous reports [8][9][10][11][12][13], prophylactic antibiotics can be necessary at least until vaccination, although there still remains controversy.…”
Section: Discussionmentioning
confidence: 99%
“…However, no standard of care for preventing meningococcal infection before immunization with meningococcal vaccine has been established. Previous studies have shown that prophylactic antibiotics were administered to infants with aHUS before or in parallel with eculizumab therapy [8][9][10][11][12][13]. Here we report our recent experience in two blood relative infants, a 4-month-old and a 5-month-old, who developed aHUS and were managed with prophylactic amoxicillin (20 mg/kg/day) [14] to prevent meningococcal infection from the beginning of eculizumab therapy to immunization with meningococcal vaccine.…”
Section: Introductionmentioning
confidence: 99%